Aggretsuko. Meet her world - Muldoon, Molly, 1987-; Griggs, Annie; Radford, Danielle; McDonald, Kel (Oni Press, 2021)
Take a journey into the sometimes wonderful world of Retsuko, the very angry red panda. Based on the hit Netflix show, AGGRETSUKO MEET HER WORLD contains three complete stories from creators Molly Muldoon, Kel McDonald, Annie Griggs, Abigail Starling, Danielle Radford, and Shadia Amin. Retsuko navigates the worlds corporate committees, girls night out, and profession wrestling in this collection featuring Aggretsuko Meet Her World #1-3.